VARIOUS METHODS IN ENLARGING STUDENTS’ VOCABULARY AND TECHNIQUES IN SPEECH ASSIMILATION - Qaypova, B.; Kalbaeva, U. (SCIENCE and SOCIETY, 2022)
The article discusses several methods and techniques for increasing the vocabulary of students in English. Opinions and conclusions of scientists are analyzed on this topic.